Is it my turn or your turn? Overlapping talk in an online interaction - Saad, Mohammad Azannee (Asia Pacific Institute of Advanced Research, 2021)
Lack of shared physical space and sometimes, visibility of the interlocutors in online interaction certainly interfere with the smooth organisation of turn-taking. In addition, to many other problems that may arise, overlapping talk between interlocutors can also take place. Overlapping talk prevents interlocutors from processing the received information clearly. It also creates a non-conducive environment because more than one speaker speaks at the same time. This study first describes interactional features leading to instances of overlapping talk and later, analyses how interlocutors linguistically repair the problematic instances. Data come from a close to 4 hours of online interaction between instructors and university students. They were recorded and transcribed following the Jefferson Transcription System (2004). On the other hand, analysis procedures were guided by the framework of Conversation Analysis by extracting instances where overlapping talks occurred. By looking into these instances, causes for overlapping talks in online interaction are reported alongside with linguistic resources that interlocutors employed to repair. Information obtained can provide understanding on one feature of online interaction and at the same time, be used as a guide to navigate a more conducive online interaction.